Randomized Clinical Trial of Extending the Time Window of Endovascular Therapy in the Triage of Late Presenting Stroke Beyond 24 h (SKIP-EXTEND): Rationale and Study Protocol - Kentaro SUZUKI; Yuji MATSUMARU; Masataka TAKEUCHI; Masafumi MORIMOTO; Junya KANEKO; Keigo SHIGETA; Tomoji TAKIGAWA; Takehiro KATANO; Junya AOKI; Mikito HAYAKAWA; Toshiaki OTSUKA; Shigeru FUJIMOTO; et al. (Neurologia Medico-Chirurgica)
The therapeutic time window for endovascular therapy in acute stroke patients with large-vessel occlusion was extended to 24 hours from onset. Although a retrospective study showed the efficacy of endovascular therapy beyond 24 hours from the last known well, it remains unclear whether endovascular therapy is effective. Extending the time window of Endovascular therapy in the Triage of Late Presenting Strokes beyond 24 h (SKIP-EXTEND trial) aimed to clarify the efficacy of endovascular therapy compared to the best medical management. This is an investigator-initiated, multicenter, prospective, randomized, open-label, blinded end-point clinical trial. Eligibility criteria included adults and pre-stroke modified Rankin scale score 2 with internal carotid artery or M1 (horizontal or sphenoidal segment) occlusion beyond 24 to 72 hours of the last known well. The target enrollment is 260 patients, with 130 reeiving endovascular therapy and 130 receiving the best medical treatment. The primary outcome is the rate of favorable outcome defined as a modified Rankin scale score 2 at 90 days. The secondary outcomes are the ordinal logistic regression analysis of the modified Rankin scale score and the rate of recanalization at 48 hours. As safety outcomes, the rate of any and symptomatic intracranial hemorrhage at 24 hours and the rate of mortality at 90 days are assessed. This is the first randomized controlled trial to focus on the efficacy of endovascular therapy beyond 24 hours. Our results will not only benefit patients but also reduce healthcare costs. We believe that this novel study will be useful in clinical practice.